Konstruksi Fikih Wanita dalam Buku Ajar Pendidikan Agama Islam Kurikulum Merdeka: Studi Analisis Konten - Putri Syifa Maudi; Udin Supriadi; Cucu Surahman (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
The Merdeka Curriculum is expected to be a strategic medium in building the rationale for gender justice, but empirical reality shows indications of perpetuating patriarchal bias that marginalizes the role of women. This research analyzes the construction of women's fiqh material in three official state-published PAI high school/vocational school textbooks (Grades X, XI, XII) to assess their alignment with gender equality principles and maqāṣid al-syarī'ah. Using Qualitative Content Analysis based on Berger and Luckmann's social construction theory, the study finds systemic gender bias through three typologies: prohibition orientation (Grade X), domestification of marriage roles (Grade XI), and focus on inheritance rights differentiation (Grade XII). A latent absence was also found in the exclusion of the right to khulu', leadership, and representation of female scholars. The material on women's fiqh has been identified as partial and subordinative, not yet reflecting the value of protecting human dignity mandated by maqāṣid al-syarī'ah, thus requiring substantive reform in the evaluation and preparation of the national PAI textbooks.